ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL KERIPIK PISANG DI KABUPATEN LUMAJANG - Maghfirah, Annisa Nurul; Anggraeni, Puspita Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The unemployment rate in Lumajang Regency is still relatively high because of the large population and low quality of education. This is because the existence of a small banana chip industry in Lumajang Regency can contribute to absorbing labor and reducing unemployment. This study aims to determine the effect of the variables of capital, amount of production, education level, and wages on labor absorption variables in the small banana chip industry in Lumajang Regency. This study uses secondary data from the Central Statistics Agency (BPS) and the Lumajang Regency Trade Office to determine the number of small banana chip industries in Lumajang Regency. This study also uses primary data, namely a questionnaire with a cross section data model of 40 banana chip entrepreneurs in Lumajang Regency with the selection of a simple random sampling model. The analytical method used is multiple linear regression analysis using the application of Statistical Product and Service Solutions (SPSS). Simultaneous test results show that the variables of capital, total production, education level, and wages have a significant effect on employment in the small banana chip industry in Lumajang Regency. While the partial test results show that capital, total production, education level, and wages have a significant effect on employment in the small banana chip industry in Lumajang Regency.